2012
DOI: 10.2903/j.efsa.2012.2674
|View full text |Cite
|
Sign up to set email alerts
|

Scientific Opinion on the safety and efficacy of folic acid as a feed additive for all animal species

Abstract: Folic acid, a synthetic folate compound, is converted in animals to biologically active folates. These are essential for DNA synthesis, repair and methylation, in particular nucleotide biosynthesis and remethylation of homocysteine. Oral administration routes of folic acid via feed or water for drinking are considered bioequivalent. Folic acid is safe for the target animals and there is no need to define a maximum content in feed. Population exposure to folic acid/folates in Europe is below the tolerable upper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…Some studies were identified in the literature search reporting deposition of folates in food of animal origin. The FEEDAP Panel noted that new data derived from publications by Tactacan et al (2012), Altic et al (2016) and Bagheri et al (2019), all concerning deposition in the eggs, give very similar values to those retained in the former EFSA assessment (EFSA FEEDAP Panel, 2012). The study by Czarnowska-Kujawska et al (2020) concerning the deposition of folates in livers of chickens, turkeys, pigs and beef collected in retail/butchers, shows high deposition values however, no information was provided in the publication whether the samples were obtained from animals fed with folic acid-supplemented diets.…”
Section: Safety For the Consumersmentioning
confidence: 81%
See 3 more Smart Citations
“…Some studies were identified in the literature search reporting deposition of folates in food of animal origin. The FEEDAP Panel noted that new data derived from publications by Tactacan et al (2012), Altic et al (2016) and Bagheri et al (2019), all concerning deposition in the eggs, give very similar values to those retained in the former EFSA assessment (EFSA FEEDAP Panel, 2012). The study by Czarnowska-Kujawska et al (2020) concerning the deposition of folates in livers of chickens, turkeys, pigs and beef collected in retail/butchers, shows high deposition values however, no information was provided in the publication whether the samples were obtained from animals fed with folic acid-supplemented diets.…”
Section: Safety For the Consumersmentioning
confidence: 81%
“…The safety of the additive was evaluated in a previous EFSA opinion (EFSA FEEDAP Panel, 2012). The FEEDAP Panel concluded that folic acid was safe for the target animals, the consumers and the environment.…”
Section: Safetymentioning
confidence: 99%
See 2 more Smart Citations